DARI KRITIS KE TINDAKAN KOMUNIKATIF : (Kritik Jürgen Habermas terhadap Modernitas dan Rasionalitas) - M. Ied Al Munir (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
Jürgen Habermas’s Theory of Communicative Action is important to respond to modernity, rationality, and capitalism. This theory departs from the refinement of the Critical Theory stagnation promoted by the Frankfurt School’s first generation with the characters Max Horkheimer, Theodor Adorno, and Herbert Marcuse. Therefore, this study aims to describe the efforts that have been made by Habermas, both to find the cause of the stagnation of the Critical Theory and to improve it. This research is qualitative research with a literature background so data collection is done by reading the works of Habermas and other related works. Data analysis of the collected data was carried out using historical and interpretation methods. This study found that the Critical Theory proposed by Horkheimer, Adorno, and Marcuse stagnated because they interpreted rationality as instrumental rationality. Meanwhile, Habermas’s refinement of Critical Theory led to the formation of the Critical Theory in a modified form, namely the Theory of Communicative Action. In this case, Habermas’ Theory of Communicative Action provides a solution in the form of additional elements of communication for the Critical Theory and sees rationality as communicative rationality that allows interaction between subjects in social life.